Análise da evolução dos processos de recrutamento e seleção: utilização de ferramenta de automação nos processos seletivos com foco na gestão por competência - Davi, Sabrina Maria de Almeida (Universidade Federal Rural do Semi-Árido, 2021)
It is common sense that technology has been a great ally in organizational processes, bringing many benefits linked to operational efficiency. According to human resources technology company Gupy (2021), 52% of talent acquisition leaders think the hardest part of recruiting is selecting candidates from a large number of applicants. Embraer, a Gupy client, increased its assertiveness in the screening of candidates by 70%, against 20% previously, using an A.I. In this context, this work aims to analyze the evolutionary process of recruitment and selection using an integrated management system, contributing to standardization and increased efficiency, considering competency management as an essential element for defining the process. This research is qualitative in nature, where the experimental method was used in a company in the road transport industry, comparing the process manual and automated recruitment and selection, showing the benefits, advantages and disadvantages of applying a management tool in this segment, where it was possible to see improvements in the result, problems mainly in relation to the candidates' behavioral skills
Keywords: Recrutamento e seleção; Sistemas de gestão; Gestão por competência; Recruitment and selection; Management systems; Competency-based management; ENGENHARIAS::ENGENHARIA DE PRODUCAO